Perlindungan Hukum terhadap Korban Tindak Pidana Perdagangan Orang : Studi Kasus di Polrestabes Surabaya - Okta Rifo Fauziyah; Yana Indawati (Referendum : Jurnal Hukum Perdata dan Pidana, 2025)
Human trafficking is a highly complex form of transnational crime involving transnational criminal networks. This crime generally originates from developing countries with unstable socio-economic conditions, where women and children are often the primary victims. They are forced or tricked into working in exploitative sectors, particularly sexual exploitation, labor exploitation, and other forms of oppression that benefit agents, distributors, and organized crime syndicates. In Indonesia, regulations regarding this crime are stipulated in Law Number 21 of 2007 concerning the Eradication of the Crime of Human Trafficking. This study aims to determine the form of legal protection provided to victims of human trafficking in the jurisdiction of the Surabaya Police, as well as to understand the various obstacles faced by police officers and the efforts made to overcome them. The research method used is empirical juridical, namely examining the law in practice through primary data obtained from interviews, observations, and official documents, then combined with secondary data in the form of legal literature, laws and regulations, and tertiary legal materials to support the analysis. This study found that the Surabaya City Police have implemented legal protection measures for victims of human trafficking in accordance with applicable regulations, from handling reports and conducting investigations and inquiries, to coordinating with relevant agencies such as social services, women's and children's protection agencies, and non-governmental organizations. However, several obstacles remain, including limited police resources, low victim awareness of reporting cases, and threats from perpetrators that discourage victims from cooperating. Despite this, maximum efforts continue to be made through improved inter-agency coordination, legal and psychological assistance for victims, and firm law enforcement against perpetrators. Therefore, it can be concluded that legal protection for victims of human trafficking at the Surabaya City Police has been quite effective, although institutional strengthening and increased public legal awareness are still needed.